ENHANCING FIRM VALUE : THE IMPACT OF GOOD CORPORATE GOVERNANCE AND INTELLECTUAL CAPITAL, MODERATED BY LIQUIDITY - Suhardjo, Suhardjo; Murtanto, Murtanto (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
This research aimed to obtain an overview of good corporate governance, intellectual capital, and liquidity designed to help build a trusted corporate environment, transparency, and accountability in order to build long-term relationships related to investment, financial stability, and business integrity, in supporting the firm's growth in the form of price book value. The research methodology employed in this study entailed conducting multiple linear regression analysis using SPSS version 22. The sample comprised 101 companies operating in the primary consumer goods sub-sector (consumer non-cyclicals) and listed on the Indonesia Stock Exchange (IDX). Data was collected for the period spanning from 2016 to 2020. The study's findings indicated that hypothesis 2 and hypothesis 3 were accepted, indicating that both intellectual capital and liquidity exerted a positive and significant impact on the firm value of the companies.